LITERATURE REVIEW : PERAN SOCIAL MEDIA TERHADAP STRATEGI KOMUNIKASI PEMASARAN PRODUK - Putrifasari, Syelfanda; Derosa, Sania; Latando, Evrina; Nusantari, Sekar; Rizqi, Dion (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2023)
Social the media has become a force new communication and social the media has played an important role as a brand and a marketing tool for companies around the world. Method usedin this research is Systematic Literature Review (SLR). There is 1 international literature and 18 national literature contained in this article and sourced from the Google Scholar site. Social media has served as a marketing communication tool, increasing brand awareness (brand awareness), influencing consumer involvement and behavior (consumer engagement and behavior), and the company's efforts to use social media as a product communication strategy. The conclusion in this article is social media as platform play an important role in developing communication strategy for product marketing in today's digital era. Company must communicate the product well, so that it reaches the minds of consumers. Marketers are strongly advised to use a variety platform social media. For Further research is suggested to discuss more social media in terms of its weaknesses, so that readers can compare in terms of its successes and weaknesses to avoid various things that can causing losses to the business being run